Seizure-Induced Acute Glial Activation in the in vitro Isolated Guinea Pig Brain - Vila Verde, Diogo; de Curtis, Marco; Librizzi, Laura (Frontiers in Neurology, 2021)
It has been proposed that seizures induce IL-1β biosynthesis in astrocytes and increase blood brain barrier (BBB) permeability, even without the presence of blood borne inflammatory molecules and leukocytes. In the present study we investigate if seizures induce morphological changes typically observed in activated glial cells. Moreover, we will test if serum albumin extravasation into the brain parenchyma exacerbates neuronal hyperexcitability by inducing astrocytic and microglial activation. Methods: Epileptiform seizure-like events (SLEs) were induced in limbic regions by arterial perfusion of bicuculline methiodide (BMI; 50µM) in the in vitro isolated guinea pig brain preparation. Field potentials were recorded in both the hippocampal CA1 region and the medial entorhinal cortex. BBB permeability changes were assessed by analyzing extravasation of arterially perfused fluorescein isothiocyanate (FITC)–albumin. Morphological changes in astrocytes and microglia were evaluated with tridimensional reconstruction and Sholl analysis in the ventral CA1 area of the hippocampus following application of BMI with or without co-perfusion of human serum albumin. Results: BMI-induced SLE promoted morphological changes of both astrocytes and microglia cells into an activated phenotype, confirmed by the quantification of the number and length of their processes. Human-recombinant albumin extravasation, due to SLE-induced BBB impairment, worsened both SLE duration and the activated glia phenotype. Discussion: Our study provides the first direct evidence that SLE activity per se is able to promote the activation of astro- and microglial cells, as observed by their changes in phenotype, in brain regions involved in seizure generation; we also hypothesize that gliosis, significantly intensified by h-recombinant albumin extravasation from the bloodstream to the brain parenchyma due to SLE-induced BBB disruption, is responsible for seizure activity reinforcement.